2013
DOI: 10.1007/s00267-013-0176-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Degradation of Abandoned Farmlands for Conservation of the Monte Desert Biome in Argentina

Abstract: Land abandonment is a major issue worldwide. In Argentina, the Monte Desert is the most arid rangeland, where the traditional conservation practices are based on successional management of areas excluded to disturbances or abandoned. Some areas subjected to this kind of management may be too degraded, and thus require active restoration. Therefore, the aim of this study was to assess whether passive succession-based management is a suitable approach by evaluating the status of land degradation in a protected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 40 publications
3
3
0
Order By: Relevance
“…Overall, results of this study conform to those of previous studies, which showed that under severely degraded lands, self-restoration processes are hindered [69][70][71]. Such conditions negate the effectiveness of passive restoration means, and necessitate active intervention means for commencing restoration processes.…”
Section: General Discussion and Implicationssupporting
confidence: 87%
“…Overall, results of this study conform to those of previous studies, which showed that under severely degraded lands, self-restoration processes are hindered [69][70][71]. Such conditions negate the effectiveness of passive restoration means, and necessitate active intervention means for commencing restoration processes.…”
Section: General Discussion and Implicationssupporting
confidence: 87%
“…However, when analyzing the landscape as a whole, only the nutrient cycling index was significantly higher in old fields. This lack of significant differences in stability and infiltration indexes, are consistent with results found in Yannelli et al (2014). Here, we showed that even though the vegetation cover may have improved over time in old fields, the current cover might not be enough to prevent further degradation by erosion, which is related to the stability and infiltration index.…”
Section: Passive Restoration and The Implications For Management And ...supporting
confidence: 91%
“…Abandoned lands provide an opportunity to analyze the development of self-sustaining systems (Benayas et al, 2007), and are paramount for conservation and management of biodiversity and natural ecosystem processes (Yannelli et al, 2014). Recently it has been reported that farmland abandonment may constitute a unique opportunity to restore native forest systems and forest ecosystem services in Europe (Proenc ¸ a et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The species richness of the community increased in the first 15 years after abandonment [ 100 , 102 , 141 ]. However, Yannelli et al [ 142 ] reported that, in arid regions, natural succession may not be the best method for ecological restoration, and soil erosion may occur during succession, preventing the establishment of a vegetation cover. Restoration should be adapted to local conditions, taking into account environmental factors such as climate and topography in different regions.…”
Section: Resultsmentioning
confidence: 99%